Policy-Capturing on Selected Materiality Judgments. - Boatsman, James R.; Robertson, Jack C. (The Accounting Review, 1974)
Abstract The article informs that the purpose of this research was to obtain empirical insight into the concept of materiality in external reporting by constructing a mathematical model to describe the way in which a sample of knowledgeable individuals believed materiality judgments ought to be made. A set of 30 hypothetical cases was developed as an experimental instrument. Each case involved either a gain or loss on a noncurrent asset, a change in accounting principle or an uncertainty. In order to insure face validity the cases were developed to conform with parameters estimated from 103 actual financial reporting situations. The 30 cases were administered in a field experiment to 18 partners in national public accounting firms and 15 securities analysts. These subjects were instructed to categorize each case as requiring three alternative types of disclosure. By using the subjects' evaluations as a criterion and the 8 materiality variables as predictors, a multiple discriminate model was developed and validated that replicated the judgmental process of the subjects with 63% accuracy. The model was 84% accurate in discriminating between immaterial cases and material cases.